Recurrent rheumaticactivity in rheumatic heart disease - Manuj Kumar Sarkar; Rishu Mishra; Parth Pandya; Ankit Anil Chellani; Nelson Ghosh (International Journal of Medical Research and Review, 2016)
Introduction: Acute rheumatic fever (ARF) is caused by autoimmune effect of group A streptococcal infection (GAS). Cardiac involvement is typically pancarditis. Valvular damage persists after the improvement of acute episode of ARF, the persistent valvular defect and its sequel is called rheumatic heart disease (RHD). People with previous episode of ARF are at increased risk of developing newer episodes of ARF and it increases the severity of valvular damage. Thus RHD gradually worsens in patients with recurrent attacks of ARF. Frequent episodes of ARF can be prevented by secondary prophylaxis.Methods and Materials: All diagnosed cases of RHD were includedand non RHD patients were excluded from this study. Proper history, detailed physical examination, routine laboratory test, ECG and echocardiography were done in all patients. Recurrent rheumatic activity was diagnosed on the basis of modified Jones criteria’1992 and who criteria of 2004.Results: Among 100 patients studied, 45 cases were hospitalised because of heart failure due to poor compliance of medications, 38 had acute attack of rheumatic fever, and 17 cases were having lower respiratory tract infection. Thus the incidence of acute rheumatic activity in established RHD was 38%. 50% patients were on penicillin prophylaxis and 10% were on oral tablets of penicillin or azithromycin for secondary prophylaxis. It means 60% of the patient population was on secondary prophylaxis.Conclusion: Recurrent rheumatic activity is a hidden cause of morbidity and mortality in established cases of RHD as penicillin prophylaxis is not adequate because of poor compliance to the drug.